Thermodynamic Concept of Nanotechnological Processes Reagent-Free Water Treatment in Heat and Power Systems of Construction - Zhuravska, Nataliia; Kulikov, Petro (International Journal of Engineering and Technology, 2018)
In the article the thermodynamic concept of nanotechnological processes of non-reagent preparation of technical water of thermal power engineering enterprises is considered. The thermodynamic functional characteristic is presented in heat energy systems of construction with non-reagent water treatment in electromagnetic fields. It is noted, with regard to biological impurities in water, that this method eliminates the accumulation of salts in the pipeline, biological damage, as the emergence of potentially possible critical technogenic situations.Â Â Â